Decreased in‐hospital mortality rate following implementation of a comprehensive electronic medical record system. (6th September 2021) - South, Mike; Cheng, Daryl; Andrew, Lauren; Egan, Nicholas; Carlin, John
Abstract : Aim: To evaluate changes in in‐hospital mortality rate following implementation of a comprehensive electronic medical record (EMR) system. Methods: Before and after study of 355, 709 hospital discharges, over an 8‐year period, at a paediatric teaching hospital. The major outcome measures were crude number of in‐hospital deaths, deaths per 1000 discharges, and standardised mortality ratio. Results: Primary analysis of data from 2 years before and 2 years after EMR go‐live showed a reduction in absolute mortality of 33 deaths, a reduction in the mortality rate of 0.48 per 1000 discharges (95% CI 0.09, 0.88 per 1000): and a relative 22% decrease (95% CI: 4%, 36%, P = 0.02) in deaths per 1000 discharges from 2.20 to 1.72. There was also a reduction in standardised mortality ratio of 47% (95% CI: 18%, 66%, P = 0.004). Post‐hoc analysis of mortality rates for an additional 2‐year pre‐intervention period indicated that these changes in the mortality rate were not part of a pre‐existing downward trend. Further analysis of an additional 20‐month post‐intervention period suggests that the reduced mortality rate has been sustained. Conclusion: We documented evidence of a clinically important decrease in in‐hospital mortality rate following the implementation of a modern comprehensive EMR system in an Australian paediatric teaching hospital. The study does not prove a causal relationship, and it is possible that other factors explain some, or all, of this difference, but no changes in the hospital population or other major interventions were identified as alternative explanations for this observed change.